Electrosteric Activation by using Ion‐Tagged Prolines: A Combined Experimental and Computational Investigation. Issue 10 (15th August 2013) - Bottoni, Andrea; Lombardo, Marco; Miscione, Gian Pietro; Montroni, Elisa; Quintavalla, Arianna; Trombini, Claudio
Abstract We have recently proposed the empirical concept of electrosteric activation to explain the improved catalytic performances observed for a series of ion‐tagged catalysts compared to the parent tag‐free structures. Here, the results of a combined experimental and computational investigation on the asymmetric aldol reaction between cyclohexanone and benzaldehyde, catalyzed by a family of tag‐free and ionic‐tagged prolines, are presented. Whereas diastereo‐ and enantioselectivities remain very high in all cases examined, the ion‐tagged catalyst cis‐4‐(2‐(3‐methyl‐imidazol‐3‐ium‐1‐yl)acetoxy)‐proline bistriflimide, cis‐7, displays a remarkably high activity compared to its tagged trans analogue and to the tag‐free catalysts cis and trans‐4‐(2‐phenylacetoxy)‐proline 8. A computational investigation of ion‐tagged and tag‐free model systems shows that the transition state involving cis‐7 is stabilized by a complex interplay of hydrogen bonds (in particular, those involving the counter ion oxygen atoms and the hydrogen atoms of the ionic tag), π‐stacking interactions involving the aldehyde phenyl ring, and similar π interactions between the proline carboxyl group and the imidazole ring. The overall effect of these interactions accounts for the observed enhanced activity.